Dicksonia sellowiana Hook. and Nepholepis cordifolia (L.) Lellinger extracts as potential green pesticides: insecticidal activity (Research, Society and Development, 2020)
Known as green insecticides, natural plant-based products have become a promising alternative to conventional insecticides. The primary objective of the present study was to analyze, under laboratory conditions, the insecticidal activity of crude ethanol extracts of the fern species Dicksonia sellowiana and Nephrolepis cordifolia against Oncopeltus fasciatus (Hemiptera). Fern leaves were collected from Itatiaia National Park (Brazil), dried and ground using 96% ethanol, with the extract concentrated in a rotary evaporator. The crude extract was used to prepare a 50 mg/mL solution, with acetone as solvent. Qualitative analysis of the terpenoid and phenolic substance profile in the extracts was performed by thin-layer chromatography (TLC). Fourth-instar insects were used, in groups of 10 animals per treatment, with three repetitions. Four treatments were used: D. sellowiana and N. cordifolia extracts, acetone control and water control. Then, 1 μL either of the respective solution was topically applied to the insect abdominal cuticle. After 21 days, all the insects in the water control group had reached adult. The N. cordifolia extract was responsible for 63% (p < 0.0001) of insect mortality around 16 days after treatment, whereas the D. sellowiana exhibited 50% (p < 0.0001) on the 21st day post-treatment. The extracts also caused delays in insect molting and metamorphosis. The D. sellowiana and N. cordifolia extracts exhibited 18% similarity in the terpenoid profile and 0% for phenolic substances. N. cordifolia and D. sellowiana show potential for research on selective biodegradable substances for use as green insecticides.